Stronger Sensitivity of Plant Photosynthesis to Rising CO 2 in High Elevation Ecosystems - Yao Chen; Yangjian Zhang; Zhihua Liu; Shilong Piao; Jingfeng Xiao; Ashley Ballantyne; Philippe Ciais; Josep Peñuelas; Jie Gao; Yongwen Liu; Lin Jiang; Juntao Zhu; et al. (Ecology Letters, 2026)
The CO 2 ‐fertilisation effect (CFE) on vegetation productivity is the major driver of the enhanced land carbon sink in recent decades. CFE theoretically increases with elevation due to the higher sensitivity of carboxylation to an increase of CO 2 under lower CO 2 partial pressure, but the elevation‐dependent CFE pattern has been largely overlooked. By conducting a 6‐year CO 2 enrichment experiment (+100 ppm) in an alpine grassland, we show that elevated CO 2 increased gross primary production (GPP) by 25.5% ± 4.6%. Water availability and plant biomass allocation modulates CFE during different seasons. A global synthesis of 10 CO 2 enrichment experiments reveals that CFE increased with elevation. The satellite‐based EC‐LUE model also demonstrates a positive global elevation‐dependent CFE pattern, albeit substantially weaker than that from experimental observations. Current terrestrial biosphere models, however, could not represent the elevation‐dependent pattern, highlighting the need to improve the representations of plants' elevational physiological adaptation to rising CO 2 in models.